Synthesis, Transfer, and Gas Separation Characteristics of MOF-Templated Polymer Membranes - Sophia Schmitt; Sergey Shishatskiy; Peter Krolla; Qi An; Salma Begum; Alexander Welle; Tawheed Hashem; Sylvain Grosjean; Volker Abetz; Stefan Bräse; Christof Wöll; Manuel Tsotsalas (Membranes, 2019)
This paper discusses the potential of polymer networks, templated by crystalline metal−organic framework (MOF), as novel selective layer material in thin film composite membranes. The ability to create mechanically stable membranes with an ultra-thin selective layer of advanced polymer materials is highly desirable in membrane technology. Here, we describe a novel polymeric membrane, which is synthesized via the conversion of a surface anchored metal−organic framework (SURMOF) into a surface anchored gel (SURGEL). The SURGEL membranes combine the high variability in the building blocks and the possibility to control the network topology and membrane thickness of the SURMOF synthesis with high mechanical and chemical stability of polymers. Next to the material design, the transfer of membranes to suitable supports is also usually a challenging task, due to the fragile nature of the ultra-thin films. To overcome this issue, we utilized a porous support on top of the membrane, which is mechanically stable enough to allow for the easy membrane transfer from the synthesis substrate to the final membrane support. To demonstrate the potential for gas separation of the synthesized SURGEL membranes, as well as the suitability of the transfer method, we determined the permeance for eight gases with different kinetic diameters.